RNA-Seq Analysis Reveals Hub Genes Involved in Chicken Intramuscular Fat and Abdominal Fat Deposition During Development - Xing, Siyuan; Liu, Ranran; Zhao, Guiping; Liu, Lu; Groenen, Martien A. M.; Madsen, Ole; Zheng, Maiqing; Yang, Xinting; Crooijmans, Richard P. M. A.; Wen, Jie (Frontiers in Genetics, 2020)
Fat traits are important in the chicken industry where there is a desire for high intramuscular fat and low abdominal fat. However, there is limited knowledge on the relationship between the dynamic status of gene expression and the body fat deposition in chicken. Transcriptomes data were obtained from breast muscle and abdominal fat of female chickens from 9 developmental stages (from embryonic day 12 to hatched day 180). In total, 8545 genes in breast muscle and 6824 genes in abdominal fat were identified as developmental dynamic genes. Weighted correlation network analysis was used to identify gene modules and the hub genes. Twenty-one hub genes were identified, e.g. ENSGALG00000041996, which represents a candidate for high intramuscular fat, and CREB3L1, which related to the low abdominal fat weight. The transcript factor L3MBTL1 and the transcript factor co-factors TNIP1, HAT1, and BEND6 related to both high breast muscle IMF and low abdominal fat weight. Our results provide a resource of developmental transcriptome profiles in chicken breast muscle and abdominal fat. The candidate genes can be used in the selection for increased intramuscular fat content and/or a decrease in abdominal fat weight which would contribute to the improvement of these traits.